2008
DOI: 10.1016/j.immuni.2008.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Human Effector and Memory CD8+ T Cell Responses to Smallpox and Yellow Fever Vaccines

Abstract: To explore the human T cell response to acute viral infection, we performed a longitudinal analysis of CD8(+) T cells responding to the live yellow fever virus and smallpox vaccines--two highly successful human vaccines. Our results show that both vaccines generated a brisk primary effector CD8(+) T cell response of substantial magnitude that could be readily quantitated with a simple set of four phenotypic markers. Secondly, the vaccine-induced T cell response was highly specific with minimal bystander effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

71
606
7
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(689 citation statements)
references
References 70 publications
71
606
7
5
Order By: Relevance
“…This molecule has recently been shown to be expressed together with HLA-DR, Ki-67 and a downregulated Bcl-2 on almost all YFV-17D-specific CD8 + T cells in the primary vaccination phase [9]. Similar to YFV-17D-specific CD4 + T cells (Fig.…”
Section: Cd8 + T Cellsmentioning
confidence: 69%
See 1 more Smart Citation
“…This molecule has recently been shown to be expressed together with HLA-DR, Ki-67 and a downregulated Bcl-2 on almost all YFV-17D-specific CD8 + T cells in the primary vaccination phase [9]. Similar to YFV-17D-specific CD4 + T cells (Fig.…”
Section: Cd8 + T Cellsmentioning
confidence: 69%
“…The systemic response to YFV-17D vaccination was analyzed on the molecular level in detail and the B-cell growth factor TNFRS17 has been identified as a predictor of height of neutralizing antibody titers [12]. Yet the early cellular events leading to such an accurate activation of all three branches of adaptive immunity have not yet been elucidated in detail, as so far most studies focused on later time points [7][8][9][10].In order to decipher the immunological processes inducing a robust and persistent protective immune response, we have performed a detailed analysis of the activation and differentiation kinetics of various cell types of both the innate and the adaptive immune system in the course of YFV-17D vaccination. We observed activation of DCs and polyfunctional YFV-specific CD4 + T cells at early time points after vaccination, correlating with the magnitude of the neutralizing antibody response specific for YFV-17D.…”
mentioning
confidence: 99%
“…Previous studies with two highly effective vaccines in humans, the yellow fever virus (YFV) vaccine and the smallpox vaccine, have indicated measurement of cytokine-producing T cells alone may vastly underestimate the total frequency and functional diversity of vaccine-induced T-cell responses (21). Moreover, these studies, using tetramers to detect specific cells, indicated measurement of activation markers can accurately identify vaccine-induced populations of effector CD8 T cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of activated virus-specific and total CD8 T cells in 50 patients with acute HBV, dengue, influenza, and adenovirus infections show that HCMV-and EBV-specific CD8 T cells are activated, proliferate, and have increased production of IFN-ɣ during heterologous infection (Sandalova et al 2010). Conversely, vaccination for yellow fever or vaccinia virus did not induce activation or proliferation of EBVand HCMV-specific CD8 T cells, despite robust CD8 T cell responses (Miller et al 2008).…”
Section: Acute Co-infectionmentioning
confidence: 99%